207k views
4 votes
3p-3p+2s-6s+2q-3q+8r-7r

Is it ok to not put the p in this equation as the 3p is minus

User Edn
by
7.6k points

1 Answer

4 votes

Answer:

- 4s - q + r

Explanation:

that's right. You do not put the p since 3p and -3p cancel out to give zero. I'll solve the question for you:-

⇒3p-3p+2s-6s+2q-3q+8r-7r

add or subtract the like terms(terms having same variables), then out of the two like terms, put the sign of the greater number, for e.g. 2q-3q = -1q

⇒0 - 4s - 1q + 1r

⇒- 4s - q + r Answer

hope that helps...

User Peter Nimmo
by
7.4k points